Integrating camera traps and community knowledge to assess the status of the Indian pangolin Manis crassicaudata in the Eastern Ghats, India. Issue 5 (13th September 2021) - Aditya, Vikram; Komanduri, Krishna Pavan; Subhedar, Rohit; Ganesh, Thyagarajan
Abstract: Pangolins are the most trafficked animals globally. Although the Indian pangolin Manis crassicaudata occurs across the Indian subcontinent (excluding parts of the Himalayas and the north-east, where the Chinese pangolin Manis pentadactyla is present), it is categorized as Endangered on the IUCN Red List as a result of heavy poaching for its meat and scales. Several areas have not yet been surveyed for the occurrence of the Indian pangolin, one of which is the 16, 948 km 2 tropical deciduous forests of the northern Eastern Ghats landscape in Andhra Pradesh. During December 2017–April 2018, we surveyed 750 km 2 of this landscape for the presence of the Indian pangolin, using camera traps. As an alternative method to document pangolin presence, and to identify factors driving hunting of the species, we also conducted, during the same period, a total of 60 semi-structured interviews with people in 30 villages. Interviewees reported the presence of pangolins in a majority of the grid cells that we surveyed with camera traps, particularly in moist deciduous forests distant from villages. However, the camera traps did not detect pangolins in 840 trap-days. Hunting of pangolins for their meat, which is consumed locally, and for their scales, which are traded, is most likely the reason for the rarity of the species in this landscape. A better understanding of the proximate and ultimate drivers of pangolin hunting is required, to inform proactive conservation management for this increasingly threatened species.